Stearidonic Acid-Enriched Soybean Oil Increased the Omega-3 Index, an Emerging Cardiovascular Risk Marker - Harris, William S.; Lemke, Shawna L.; Hansen, Susan N.; Goldstein, Daniel A.; DiRienzo, Maureen A.; Su, Hong; Nemeth, Margaret A.; Taylor, Mary L.; Ahmed, Gulam; George, Cherian (Lipids, 2008)
A plant source of omega-3 fatty acid (FA) that can raise tissue eicosapentaenoic acid (EPA) and/or docosahexaenoic acid (DHA) is needed. A soybean oil (SBO) containing approximately 20% stearidonic acid [SDA; the delta-6 desaturase product of alpha-linolenic acid (ALA)] derived from genetically modified soybeans is under development. This study compared the effects of EPA to SDA-SBO on erythrocyte EPA + DHA levels (the omega-3 index). Overweight healthy volunteers (n = 45) were randomized to SDA-SBO (24 ml/day providing ~3.7 g SDA) or to regular SBO (control group) without or with EPA ethyl esters (~1 g/day) for 16 weeks. Serum lipids, blood pressure, heart rate, platelet function and safety laboratory tests were measured along with the omega-3 index. A per-protocol analysis was conducted on 33 subjects (11 per group). Compared to baseline, average omega-3 index levels increased 19.5% in the SDA group and 25.4% in the EPA group (p < 0.05 for both, vs. control). DHA did not change in any group. Relative to EPA, SDA increased RBC EPA with about 17% efficiency. No other clinical endpoints were affected by SDA or EPA treatment (vs. control). In conclusion, SDA-enriched SBO significantly raised the omega-3 index. Since EPA supplementation has been shown to raise the omega-3 index and to lower risk for cardiac events, SDA-SBO may be a viable plant-based alternative for providing meaningful intakes of cardioprotective omega-3 FAs.